A Case of Brucella Endocarditis in Association with Subclavian Artery Thrombosis. (10th July 2012) - Colomba, Claudia; Siracusa, Lucia; Rubino, Raffaella; Trizzino, Marcello; Scarlata, Francesco; Imburgia, Claudia; Titone, Lucina
Abstract : Brucellosis is a common zoonosis, endemic in Mediterranean countries, and caused by bacteria of Brucella genus. Brucellosis is a systemic infection and the clinical presentation varies widely from asymptomatic and mild to severe disease. Cardiovascular complications are extremely rare. We present a case of arterial thrombosis in a previously healthy young patient with Brucella endocarditis. Careful attention must be paid to any sign or symptom of thrombosis in patients affected by brucellosis, regardless of the presence of endocarditis and cardiovascular risk factors.